Music Business in the Digital Economy Age - V. S. Kazarova; A. G. Mirakyan (Вестник Российского экономического университета имени Г. В. Плеханова)
This article is devoted to the definition of new trends and managerial patterns in the music business, which are just beginning to develop as a result of the widespread expansion of digital technologies. The state of the music industry before the emergence and development of digital technologies is shown, prerequisites for radical changes are marked, in particular, the emergence of broadband Internet access and digital MP3 format, piracy and streaming technologies (streaming). The article examines the changes and new trends emerging in the music business in the digital era with the development of virtual reality, cancel culture, blockchain technologies, NFT and the sharing economy. The key changes in the overall business model and current management trends forming new determinants of the music business are shown. It is concluded that the world music industry has radically changed its appearance: the music business model itself is changing, and the general model of music information consumption is also being transformed. Music dematerializes and becomes more accessible - business players are constantly fighting for the digital attention of consumers. In general, there is a fragmentation of the music market. The authors raise topical issues that the scientific and practical community has yet to answer.